2011
DOI: 10.3390/nu3010164
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment to Underpin Food Regulatory Decisions: An Example of Public Health Nutritional Epidemiology

Abstract: The approach used by food regulation agencies to examine the literature and forecast the impact of possible food regulations has many similar features to the approach used in nutritional epidemiological research. We outline the Risk Analysis Framework described by FAO/WHO, in which there is formal progression from identification of the nutrient or food chemical of interest, through to describing its effect on health and then assessing whether there is a risk to the population based on dietary exposure estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…This means that the SD of the final distribution is 80% of the original. The lower the ratio, the higher the correction—for example, a ratio of 0.5 would have resulted in a distribution with a SD of half the width of the original 21. We do not know whether having a greater number of replicates, such as 7 or 14, or including different seasons, would have yielded the same result.…”
Section: Discussionmentioning
confidence: 96%
“…This means that the SD of the final distribution is 80% of the original. The lower the ratio, the higher the correction—for example, a ratio of 0.5 would have resulted in a distribution with a SD of half the width of the original 21. We do not know whether having a greater number of replicates, such as 7 or 14, or including different seasons, would have yielded the same result.…”
Section: Discussionmentioning
confidence: 96%
“…If F i approaches 1, then the corrected UIC for 1 day (day 1) is near the long-term UIC tendency. 19 20 Our study included the F i of different seasons, ages, sexes and settings to determine if it was different for various population subsets. The results showed that age, sex and setting subsets make little difference, whereas season has an important influence on F i .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the mandatory iodine fortification policy, high-risk groups with increased requirements, including pregnant and lactating women, may still not be adequately protected [11]. Dietary studies report an increased iodine intake in pregnant women since the implementation of fortification [12,13,14]. But these studies were not conducted in nationally representative samples of the population.…”
Section: Introductionmentioning
confidence: 99%